ANALISIS PELAYANAN PUBLIK PADA PEMBUATAN SURAT IZIN MENGEMUDI KENDARAAN RODA EMPAT (SIM A) DI SATLANTAS POLRESTA PEKANBARU - Rizko Fahri; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
City Post Office Pekanbaru in the postal service has not done well users of postal services increasingly in decline, as well as delivery service parcel post still tend to wait for delivery of packages simultaneously, which is known delivery postal packets that will be sent must wait for the fulfillment of the capacity of the car that would bring the package post so that it is experiencing delays in delivery as well as the lack of precision of acceptance parcel post which is known in the service time that is later than the delivery until the receipt of postal parcels. The purpose of this study was to determine the service provided Post Office Jalan Sudirman Pekanbaru in the delivery of postal parcels and determine the factors that affect the implementation of the Parcel Post services at the Post Office and for the city of Pekanbaru.The type and method of research is descriptive research, which is defined as the process of solving problems investigated by presenting or describing the state of the subject and object of research at the present time based on the facts that appear or as it is. In the data collection authors conducted in-depth interviews and searches documents and archives post office.The results showed that the delivery service Parcel Post with a set of standard operating procedures in yet sustainability post package delivery has not been seen in the achievement of optimum service, it is the post office is still slow in providing services due to the lack of the number of employees in providing services and lack of infrastructure available so that the service provided is not timely, the community in the delivery of postal parcels.The type and method of research is descriptive research, which is defined as the process of solving problems investigated by presenting or describing the state of the subject and object of research at the present time based on the facts that appear or as it is. In the data collection authors conducted in-depth interviews and searches documents and archives post office.Keywords: Analysis, Public Service, Postal Package delivery